Higher order turbulent flow characteristics of oscillatory flow over a wall-mounted obstacle. Issue 1 (2nd January 2020) - Singh, Santosh Kumar; Raushan, Pankaj Kumar; Debnath, Koustuv; Mazumder, Bijoy S.
Abstract: The paper presents an experimental study in a laboratory flume to investigate the combined wave–current flow over a wall-mounted cubic obstacle. Detailed velocity data were collected using three-dimensional (3D) micro-acoustic Doppler velocimeter from upstream to downstream of the cube along the centerline of the flume. This study examines the spectra, co-spectra, and turbulence kinetic energy flux analysis under the influence of cube in the turbulent boundary layer. It is observed that stream-wise spectral and co-spectral energy distributions vary with the addition of surface wave. Particular attention is also given to understand the behavior of higher order moments to explicitly account for turbulent momentum transport characteristics over wall-mounted cube under wave–current interactions.